DATA-PROCESSING TRAINING USES A SPSS APPLICATION FOR IBNU SINA UNIVERSITY MANAGEMENT STUDENTS - Ita Mustika; Septa Diana Nabella; Mulyadi Mulyadi (Yayasan Education and Social Center, 2022)
Research is one of the supporting elements in the Tri Dharma of Higher Education. For research students, it is stated in the writing of the final project, a mandatory requirement to achieve graduation. However, students who will compile their final project are usually confused about the problems they will raise because they do not have experience. I have never done the research and do not know the program used to process data. Maybe some already know but cannot use it. The training activities use presentation, discussion and practice methods. This activity was attended by 250 students of semester VII (seven) management study programs. From the results that have been carried out, it appears that the participants are enthusiastic about participating in the training. The many questions and responses evidence this participant after the devotees deliver the material and provide hands-on practice. In addition, community service activities that have been carried out have obtained results, including increased knowledge, understanding, and skills of students on how to operate the SPSS program, input and process data and read the output or interpret the results of processing the data.